CO2 emissions and expansion of railway, road, airline and in-land waterway networks over the 1985–2013 period in China: A time series analysis. (December 2017) - Li, Xin; Fan, Yingling; Wu, Lan
Highlights: Transportation development in China has long-run causal effects on CO2 emissions. Road, airline, and waterway expansions lead to long-run increases in CO2 emissions. Waterway expansion has the strongest impact on CO2, followed by road expansion. Railway expansion leads to short-run increases, and yet long-run decreases in CO2 . Abstract: China, the world's largest CO2 emitter, is continuing its long-term strategy to use transportation investments as a tool for development. With the expectation that transportation will contribute 30–40% of the total CO2 emissions in China in the near future, there is an imminent need to identify how the development of different transportation modes may have different long-term effects on CO2 emissions. Using time series data over the period of 1985–2013, this paper applies the combined autoregressive distributed lag (ARDL) and vector error correction model (VECM) approach to identify short- and long-run causal relationships between CO2 emissions and mode-specific transportation development, including railway, road, airline, and inland waterway. We find that China's domestic expansions of road, airline, and waterway infrastructure lead to long-run increases in CO2 emissions. Among them, waterway has the strongest positive impact on CO2 emissions, followed by road. Despite a short-run, positive impact on CO2 emissions, railway expansion leads to long-run decreases in CO2 emissions. The results are especially encouraging for the central government of China given its long-standing and on-going efforts to expand railway infrastructure at the national level. Looking forward, it is recommended that China continues its national investments in railway infrastructure to achieve both environment and economy goals.